OPEN-ENDED APPROACH TO IMPROVE STUDENTS' MATHEMATICAL COMMUNICATION SKILLS - Feri Haryati (International Conference on Social and Islamic Studies, 2021)
This study aims: (1) to see whether the increase in mathematical communication skills of students who receive learning with an open-ended approach is better than students who receive conventional learning, (2) describe students' attitudes towards learning with an open-ended approach. This study uses experimental research methods with nonequivalent control group design. The population in this study were all UMSU mathematics education students for the 2019/2020 academic year. Sampling using purposive sampling. The research instrument used was a test of students' mathematical communication skills, observation sheets and interview guidelines. Data analysis using T test,. The results showed that; (1) improving the mathematical communication skills of students who receive learning with an open-ended approach better than students who receive conventional learning (2) students' attitudes towards learning with an Open Ended approach are showing interest in learning by forming groups; Students show seriousness in doing the exercises; and Students show pleasure and sincerity in working on problems given by the lecturer and then present them in front of the class. Students become more confident, active and brave in expressing opinions and have confidence in answering questions given by the lecturer. It can be concluded that learning using an open-ended approach can improve students' mathematical communication skills and can increase student activity during learning. Therefore, lecturers and teachers should make learning with an open-ended approach during learning.